1999
DOI: 10.1002/(sici)1099-1026(199909/10)14:5<333::aid-ffj839>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Two chemotypes ofCrithmum maritimum L. from Portugal

Abstract: Essential oils were isolated from different parts of Crithmum maritimum L. at three stages of the life cycle (vegetative, flowering and fruiting) in the same population (central west Portuguese coast) and essential oils were also extracted from plants growing spontaneously in five parts of the Western coast of Portugal, at the three life cycle stages. GC and GC–MS analyses were carried out in order to determine the oil chemical composition. The major oil components were dillapiol, sabinene, γ‐terpinene and thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 8 publications
5
30
0
2
Order By: Relevance
“…Baser et al [7] reported sabinene (27%), c-terpinene (19.3%), limonene (24.2%) and terpinen-4-ol (9.0%) in a Turkish sample. In another study, the major compounds were reported to be dill apiol, sabinene, c-terpinene and thymol methyl ether in a sample of Portugal origin [15].…”
Section: Resultsmentioning
confidence: 99%
“…Baser et al [7] reported sabinene (27%), c-terpinene (19.3%), limonene (24.2%) and terpinen-4-ol (9.0%) in a Turkish sample. In another study, the major compounds were reported to be dill apiol, sabinene, c-terpinene and thymol methyl ether in a sample of Portugal origin [15].…”
Section: Resultsmentioning
confidence: 99%
“…The variations in the essential oils of Zingiber of¼cinale and Myristica fragans of different origins can be given as examples (Tables 5 and 6). Other examples include the essential oils of Crithmum maritimum, 41,42 Thymus carnosus 43 and T. caespititius (Santos et al 44 and references therein).…”
Section: Geographic Variationmentioning
confidence: 99%
“…A comparison between the oils obtained by SFE and by hydrodistillation revealed that their chemical differences were not relevant. Some studies previously carried out to characterize the chemical composition of C. maritimum oil [8,25] showed that two chemotypes were present among Portuguese plants: chemotype 1 with % dillapiole 414.5, and chemotype 2 with % dillapiole 55.8. The composition reported for plants growing in Italy (Sicily and Campania) [7,25] was different from our Sardinia plant: the content of dillapiole was 50.05% and 0.2%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthemore, the succulent leaves and young branches are used in folk medicine for their antiscorbutic, carminative, diuretic, digestive, purgative and vermifuge properties. It is also commonly known in the coastal areas as an excellent season salad used to accompany fish dishes [5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%